The organization of health-saving educational process in university with modern conditions. - Boreyko N.U (Kharkov National Pedagogical University, 2010)
In the article the fundamentals of health-saving educational process in accordance with the current conditions of educational modernization. The analysis of more than 30 regulatory documents and literature. The study involved 1896 students of NTU "KPI". With the help of theoretical analysis, the content, principles of health-saving educational process, identified the pedagogical conditions of health-saving system for students of technical universities. It is well-proven that for upgrading education the lead through of optimization of the educational, psychological and physical loading of students and teachers, creation in higher educational закладах of terms, is needed for a maintainance and strengthening of their health.